Literary Samizdat and Samizdat Publics (ENTHYMEMA, 2015)
In this article Komaromi considers literary samizdat journals in light of public theory. Although literary samizdat journals do not conform to classic conceptions of public speech, they do yield to more recent analyses of counter-publics proposed by Nancy Fraser and Michael Warner. Picking up on the poetic aspects of public speech highlighted by Warner, Komaromi examines the publics projected by literary samizdat journals through statements about those publics, style, and bibliographic values. While not directly contesting political conditions, these literary journals amplified the implications of samizdat production and distribution to foster plurality and human connection as a basis for a better future.
Keywords: Samizdat; Literature; Journals; Leningrad; Publics